Effect of EDTA Conditioning on Microleakage of Four Adhesive Systems in Composite Restorations - F. Shafiei; M. Memarpour (Tehran University of Medical Sciences, 2008)
Objective: Evaluating the effect of dentin conditioning with EDTA on microleakage of composite resin restorations, using two etch and rinse and two self-etch adhesives. Materials and Methods: One hundred and sixty extracted molars received class V cavity preparations right under the CEJ and were randomly divided into eight groups of 20, usingfour different adhesive systems. These adhesives included Adper Scotchbond Multi-purpose (SBMP), Adper Single Bond (SB), Clearfil SE Bond (CSEB), and Adper Prompt L-Pop (PLP). In the SBMP and SB experimental groups, EDTA was applied instead of phosphoric acid. In the CSEB and PLP experimental groups, EDTA conditioning was added to the bonding process. After thermocycling, the amount of dye penetration was evaluated using stereomicroscope. The data were analyzed using the Kruskal-Wallis and Dunn tests. Results: Two etch and rinse adhesives (SBMP, SB) showed a significantly lower micro-leakage than the two self-etch adhesives, CSEB and PLP, (P<0.05). No significant differ-ence was observed among the experimental groups. PLP and CSEB showed significantly less microleakage using EDTA conditioning (P<0.05). There was no significant difference for SBMP and SB when applying either phosphoric acid or EDTA. Conclusion: In the cases of SBMP and SB, EDTA conditioning is as effective as phos-phoric acid in preventing microleakage. In cases of CSEB and PLP, EDTA conditioning can significantly improve the sealing ability.